Higher education inclusivity: when the disability enriches the university. Issue 6 (18th September 2020) - Moriña, Anabel; Sandoval, Marta; Carnerero, Fuensanta
ABSTRACT: This article analyses the perspectives of faculty members on disability in higher education. Their testimonies give value to the attitudes and qualities of university students with disabilities and show how they influence their professional and personal development. We carried out a qualitative study, through interviews with 119 faculty members of different fields from 10 Spanish universities, who were nominated by students with disabilities for developing inclusive pedagogy. We conducted a progressive analysis of the data using a system of categories and codes. The results describe the motivations that drove the participants to respond to the needs of students with disabilities, the personal and professional impact posed by the challenge of adjusting the teaching and learning processes, and the perceptions of the faculty members toward the contributions of these students to the university. In the conclusions section, we delve into the need of universities to embrace inclusivity. The data provided by this study reveal that disability can be a valuable asset in a university context that dissociates from the deficit lens and acknowledges that all students are important and able to learn when the attitudes and conditions are appropriate.